Peran Penting Housekeeping dalam Menjaga Kepuasan Tamu Hotel Patra Cirebon - Purnomo, Pungky Dios; Rahayu, Enik (Mahesa Research Center, 2025)
This study aims to examine the role of housekeeping services in enhancing guest satisfaction at Hotel Patra Cirebon. Quality housekeeping service is a crucial factor in creating a comfortable, clean, and pleasant stay experience. This research uses a descriptive qualitative approach with data collection techniques including questionnaires, in-depth interviews, and direct observations of housekeeping activities and guest perceptions. The findings reveal that guest satisfaction with housekeeping services is very high, with the majority of guests expressing great satisfaction with room cleanliness and the professional attitude of the staff. However, there are some concerns regarding service speed during peak occupancy periods. Supporting factors contributing to the success of these services include the consistent implementation of standard operating procedures (SOP), regular staff training, the use of modern equipment, and a responsive complaint handling system. The study concludes that strategic and professional management of housekeeping services not only enhances guest satisfaction and loyalty but also strengthens the image and competitiveness of Hotel Patra Cirebon in the hospitality industry. These findings provide practical recommendations for hotel management in designing sustainable service quality improvement strategies.